Hormone replacement therapy leads to increased plasma levels of platelet derived microparticles in postmenopausal women - Rank, Andreas; Rösner, Sabine; Wallwiener, Lisa-Maria; Toth, Bettina (Archives of gynecology and obstetrics, 2012)
BackgroundWhereas prevention of cardiovascular diseases by hormonal replacement therapy is still part of an ongoing debate, well-defined data are available relating hormonal replacement therapy to an elevated risk of venous thrombosis and embolism. Although it seems that venous thrombosis in patients treated with hormonal replacement therapy is linked to changes in plasmatic coagulation, less is known about the role of platelet-derived microparticles, as well as endothelial cell-derived microparticles.Patients and methodsIn this prospective case-control study, levels of microparticles were investigated in postmenopausal women receiving hormone replacement therapy (n = 15) and compared to age-matched controls (n = 15).ResultsTotal count of microparticles and the subgroup of microparticles derived from endothelial cells did not differ in the investigated groups. In contrast, median levels of microparticles derived from platelet/megacaryocyte were higher in women taking hormonal replacement therapy (5,244 × 106/l) than in controls (2,803 × 106/l; p = 0.040). Furthermore, hormonal replacement therapy led to a higher plasma level of microparticles derived from activated platelets, exposing P-selectin (136 × 106/l vs. 58 × 106/l; p = 0.011), or exposing CD63 (171 × 106 vs. 91 × 106/l; p = 0.011) compared to the control group.ConclusionHigher concentrations of microparticles derived from (activated) platelets/megacaryocytes were present in postmenopausal women taking hormonal replacement therapy. This finding indicates a procoagulant state in these women and might play a role in the development of venous side effects. In contrast, levels of endothelial cell-derived microparticles did not differ.